Innovation ecosystems and strategy in the COVID-19 crisis - Oliveira, Wesley da Paixão de (2021)
The COVID-19 pandemic is a disturbance that forced enterprises to rethink their strategies and ecosystems to keep running. Nevertheless, there is a lack of prior register to show the best policies to adopt in such circumstances. Hence, researchers and practitioners must comprehend how companies are responding to this unprecedented health crisis. Furthermore, it is of equal importance to comprehend the pandemic consequences on ventures’ strategies and ecosystems. In this sense, the research identified how four ventures handled such a situation. Through a multiple and holistic case study, supported by exploratory and qualitative approaches, the research provided a detailed description of their competitive strategies, innovation ecosystems, and the adopted measures against the crisis. The main findings were as follows: (i) The pandemic affected the studied ventures and ecosystems at different levels. The crisis severely hit the approached enterprises and ecosystems from the event and consultancy industries, especially the former. For example, the former entirely ceased their activities for a while, impacting the ecosystem activity flow. However, the pandemic boosted the businesses of the organizations and ecosystems from the telehealth and medication industries. For example, the medication case showed no change in its ecosystem composition and further capitalized from new projects that emerged due to the COVID-19 disruption. (ii) The ventures proposed changes related to the value proposition, interaction process, and activities and information flow across the ecosystem to keep running. For example, those severely affected by the COVID-19 succeeded in delivering their solutions entirely online (the consultancy industry case) or avoiding crowds (the event industry case). Further, those less affected benefited by adopting work from home (the medication industry case) or serving occupational health and safety care entirely online (the telehealth industry case). (iii) The enterprises employed these modifications mainly by adopting (the medication and telehealth industries cases) or increasing (the event and consultancy industries cases) digital solutions internally and crosswise the ecosystems. Therefore, the studied cases' competitive strategy and innovation ecosystems goals have not changed due to the pandemic: what changed was the means to achieve these objectives to respond to the crisis and keep moving forward.